Public space in different cultural conditions: The cases of Glasgow and Poznań - Ewertowski, Wojciech (Quaestiones Geographicae, 2023)
Public spaces are among the most important components of the contemporary city. They are supposed to be places of vibrant social life, where a broad set of activities and behaviours can be observed. However, the role of public spaces as well as their spatial features can differ in various societies. The built environment, as a human creation, is affected by many social factors and one of them is culture. Thus, cultural conditions can have an impact on how urban space is created, perceived, and used. Those differences are most clearly visible in distant cultures, but they may occur to a greater or lesser extent within a single culture circle. Public spaces, because of their accessibility, egalitarianism, and wide range of users are especially useful as an area of research on the relationship between space and culture. This paper presents differences between Glasgow (United Kingdom) and Poznań (Poland) in the perception and attitude towards urban public space concerning cultural conditions. The theoretical background of the relations between space and culture, and the contemporary views of public space are discussed. Afterwards, the results of the survey study conducted in both cities are presented. The research results are discussed in the context of cultural differences derived from the cultural models and show that cultural dimensions can be used to explain the activity of users of urban public spaces. They also indicate that the variety in behaviour patterns and approaches to public space can be observed within the European cultural circle.